2020
DOI: 10.1007/s00018-020-03663-z
|View full text |Cite
|
Sign up to set email alerts
|

Growth cone repulsion to Netrin-1 depends on lipid raft microdomains enriched in UNC5 receptors

Abstract: During brain development, Uncoordinated locomotion 5 (UNC5) receptors control axonal extension through their sensing of the guidance molecule Netrin-1. The correct positioning of receptors into cholesterol-enriched membrane raft microdomains is crucial for the efficient transduction of the recognized signals. However, whether such microdomains are required for the appropriate axonal guidance mediated by UNC5 receptors remains unknown. Here, we combine the use of confocal microscopy, live-cell FRAP analysis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…Similar to the DCC receptor, association with raft membranes has also been proven to be essential during axonal guidance events, as shown not only by biochemical fractionation, but also with biophysical tools. Using Fluorescence Recovery After Photobleaching (FRAP) and single-particle tracking Photoactivated Localization Microscopy (PALM), we have demonstrated that UNC5 receptors reside in raft membrane microdomains [ 100 ]. Such properties are modified after MβCD or cholesterol oxidase (ChOx) treatment [ 100 ].…”
Section: Axon Guidance Cuesmentioning
confidence: 99%
“…Similar to the DCC receptor, association with raft membranes has also been proven to be essential during axonal guidance events, as shown not only by biochemical fractionation, but also with biophysical tools. Using Fluorescence Recovery After Photobleaching (FRAP) and single-particle tracking Photoactivated Localization Microscopy (PALM), we have demonstrated that UNC5 receptors reside in raft membrane microdomains [ 100 ]. Such properties are modified after MβCD or cholesterol oxidase (ChOx) treatment [ 100 ].…”
Section: Axon Guidance Cuesmentioning
confidence: 99%
“…Netrin-1 exerts long-range chemorepulsion that is important for axonal guidance (Round & Stein, 2007), and plays a major role in the organization of EGL neurons during early postnatal development of the cerebellum, controlling the growth of parallel fibres (Alcantara et al, 2000;Hernaiz-Llorens et al, 2020;Przyborski et al, 1998). EGL neurons have been shown to co-express DCC, neogenin, DSCAM, UNC5B and UNC5C that sense Netrin-1 expressed in the EGL and in interneurons of the molecular layer of the cerebellum (Alcantara et al, 2000;Hernaiz-Llorens et al, 2020).…”
Section: Botulinum Neurotoxin C1 Decreases Netrin-1-dependent Chemorepulsion Of Egl Axonsmentioning
confidence: 99%
“…Netrin-1 exerts long-range chemorepulsion that is important for axonal guidance (Round & Stein, 2007), and plays a major role in the organization of EGL neurons during early postnatal development of the cerebellum, controlling the growth of parallel fibres (Alcantara et al, 2000;Hernaiz-Llorens et al, 2020;Przyborski et al, 1998). EGL neurons have been shown to co-express DCC, neogenin, DSCAM, UNC5B and UNC5C that sense Netrin-1 expressed in the EGL and in interneurons of the molecular layer of the cerebellum (Alcantara et al, 2000;Hernaiz-Llorens et al, 2020). To investigate whether Stx1 is necessary for Netrin-1-dependent repulsion, we co-cultured postnatal EGL explants in type I collagen 3D hydrogels, and exposed them to aggregates of either control HEK-293T cells or Netrin-1-expressing HEK-293T cells for 2 days (Alcantara et al, 2000;Hernaiz-Llorens et al, 2020).…”
Section: Botulinum Neurotoxin C1 Decreases Netrin-1-dependent Chemorepulsion Of Egl Axonsmentioning
confidence: 99%
See 2 more Smart Citations